Implementing Evidence-Informed Discharge Preparedness Tools in the NICU: Parents' Perceptions. (October 2021) - Mazur, Kathleen M.; Desmadryl, Megan; VanAntwerp, Katherine; Ziegman, Corrie; Nemshak, Michelle; Shuman, Clayton J.
Abstract : Background: Few studies address preparing parents of neonatal intensive care unit (NICU) infants for infant discharge. Inadequate or ineffective parental preparedness for discharge can result in preventable emergency department and primary care visits. Parents' perceptions are needed to inform development and implementation of effective educational tools to improve parent discharge preparedness in the NICU. Purpose: To describe the perceptions of parents of recently discharged NICU infants regarding discharge preparedness and implementation of the My Flight Plan for Home parent discharge preparedness tool. Methods: We used a qualitative descriptive design to collect individual interview data from 15 parents with infants discharged from a level 4 NICU in the Midwest. Individual interviews were conducted using a semistructured guide and were audio-recorded, transcribed verbatim, and thematically analyzed using the constant comparative method. Results: We identified 5 major themes: (1) family dynamics; (2) parenting in the NICU; (3) discharge preparedness; (4) engaging parents in infant care; and (5) implementation recommendations for the My Flight Plan for Home tool. Minor themes supported each of the major themes. Implications for Practice: To improve parents' confidence in caring for their infant after discharge, parents suggest nurses must engage parents in discharge education and infant care shortly following NICU admission and use parent-centered discharge preparedness tools. Implications for Research: Future studies are needed to develop and test parent-tailored strategies for implementing parent discharge preparedness tools in the NICU. Abstract : Supplemental Digital Content is Available in the Text.